Scaffold printing using biodegradable poly(1,4-butylene carbonate) ink: printability, in vivo physicochemical properties, and biocompatibility - Ji, Y. B.; Park, J. Y.; Kang, Y.; Lee, S.; Ju, H. J.; Choi, S.; Lee, B. Y.; Kim, M. S. (Materials Today Bio, 2021)
This study is the first to assess the applicability of biodegradable poly(1,4-butylene carbonate) (PBC) as a printing ink for fused deposition modeling (FDM). Here, PBC was successfully prepared via the bulk polycondensation of 1,4-butanediol and dimethyl carbonate. PBC was melted above 150°C in the heating chamber of an FDM printer, after which it flowed from the printing nozzle upon applying pressure and solidified at room temperature to create a three-dimensional (3D) scaffold structure. A 3D scaffold exactly matching the program design was obtained by controlling the temperature and pressure of the FDM printer. The compressive moduli of the printed PBC scaffold decreased as a function of implantation time. The printed PBC scaffold exhibited good in vitro biocompatibility, as well as in vivo neotissue formation and little host tissue response, which was proportional to the gradual biodegradation. Collectively, our findings demonstrated the feasibility of PBC as a suitable printing ink candidate for the creation of scaffolds via FDM printing.
Keywords: 3D scaffolds; Aliphatic polycarbonate; Butanediol; In vivo biodegradation; In vivo neo-tissue formation; In-vivo; Ink printability; Physicochemical property; Tissue formation; 3D-scaffold; Aliphatic polycarbonate; In vivo biodegradation; In vivo neo-tissue formation; Printing ink